Effect Of Complementary Therapy On Hypertension Patients: Systematic Review - Al Ihksan Agus; Wa Ode Sri Asnaniar; Rizqy Iftitah Alam; Haeril Amir (Universitas STRADA Indonesia, 2021)
The research was conducted using the method literature review. The literature review examines various research reports published in journals with the same focus. jurnal studies related to complementary therapies in patients with hypertension, international journal using Pubmed database, derect Science, Wiley, and DOAJ. The keywords used are